2019
DOI: 10.1039/c8cp06368k
|View full text |Cite
|
Sign up to set email alerts
|

Radiative cooling of cationic carbon clusters, CN+, N = 8, 10, 13–16

Abstract: The radiative cooling of highly excited carbon cluster cations of sizes N = 8, 10, 13-16 has been studied in an electrostatic storage ring. The cooling rate constants vary with cluster size from a maximum at N = 8 of 2.6 Â 10 4 s À1 and a minimum at N = 13 of 4.4 Â 10 3 s À1 . The high rates indicate that photon emission takes place from electronically excited ions, providing a strong stabilizing cooling of the molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…As k p is the rate constant for an activated process, it is in principle energy dependent and can therefore not rigorously be taken constant. A calculation of the leading order correction caused by the energy dependence of k p corrects fitted values of k p to the slightly different value k p (1 − hν/E a ), where hν is the energy of the photon emitting state and E a the activation energy of the observed, competing decay channel [68].…”
Section: Radiative Quenching Of Unimolecular Decaymentioning
confidence: 91%
See 2 more Smart Citations
“…As k p is the rate constant for an activated process, it is in principle energy dependent and can therefore not rigorously be taken constant. A calculation of the leading order correction caused by the energy dependence of k p corrects fitted values of k p to the slightly different value k p (1 − hν/E a ), where hν is the energy of the photon emitting state and E a the activation energy of the observed, competing decay channel [68].…”
Section: Radiative Quenching Of Unimolecular Decaymentioning
confidence: 91%
“…An oscillatory pattern then appears with RF cooling for C − 4 [69,70], VC for C − 5 [94], RF cooling for C − 6 [70,[96][97][98], and VC for C − 7 [95]. Experiments on positively charged C + N clusters, in contrast, indicate RF cooling for all the non-fullerene sizes measured, N = 8, 10, 13 − 16 [68], with rate constants scattered around 10 4 s −1 . The consistently higher rates for these clusters may be caused by the higher internal energies per degree of freedom of these species compared with the anions.…”
Section: Decays Of Carbon-based Clustersmentioning
confidence: 91%
See 1 more Smart Citation
“…The experiments reported here measured the radiative quenching time for a number of cationic carbon clusters of medium size. They extend the measurements of the limited size range reported in [16] to a number of cluster sizes not previously produced in sufficient intensities to make the experiments feasible. For clusters C + 11 and C + 19 the measurements of spontaneous unimolecular decay quenching was supplemented by measurements of the decay rates induced by one-photon absorption at varying storage times, providing a test of the assumption of a statistical decay and broad initial cluster energy distributions.…”
Section: Introductionmentioning
confidence: 87%
“…[10,[12][13][14][15] for PAH molecules and other carbon-containing ions. Studies of radiative cooling of cationic carbon clusters were reported in [16]. Also the direct detection of photons emitted from size selected clusters in such processes has been accomplished recently, with the observation of thermal, visible photons emitted from C − 6 and C − 4 [17,18] and of naphthalene ions [19].…”
Section: Introductionmentioning
confidence: 99%